On the origin and meaning of the Assyrian toponym Tabal - Giusfredi, Federico; Pisaniello, Valerio; Rizza, Alfredo (ARAMAZD: Armenian Journal of Near Eastern Studies, 2022)
The toponym Tabal was used by the Iron Age Assyrians to refer to a group of Luwian kingdoms and principalities that occupied Cappadocia during the first centuries of the Iron Age. The name itself was not used by the Luwians and it is debated whether or not it was continued in later traditions, such as the Biblical one. It thus seems to be a specific exonym reflecting an Assyrian (and possibly Canaanite) point of view. Nevertheless, an Assyrian etymology has been recently criticized, and few alternative analyses, including a Luwian and a Hurrian one, have been suggested. Admittedly, however, all of these hypotheses present formal and historical unsolved problems. In this paper we will (1) review the reasons why a Hurrian and a Luwian derivation do not hold water; (2) examine the real semantics of the Semitic root *’BL as it appears in Akkadian tābalu and nābalu; (3) propose an alternative analysis based on the linguistic profile and history of the cultures of Mesopotamia and Syro-Anatolia.